Shape Regulation of CeO2 Nanozymes Boosts Reaction Specificity and Activity. Issue 20 (10th June 2022) - Tan, Zicong; Wang, Ying; Zhang, Jie; Zhang, Zhang; Man Wong, Samantha Sze; Zhang, Shiqing; Sun, Hongyan; Yung, Ken Kin Lam; Peng, Yung‐Kang
Abstract: Among reported nanozymes, CeO2 seems to be the only transition metal oxide that can mimic phosphatase and peroxidase by catalyzing substrate dephosphorylation and oxidation (with H2 O2 ). However, no consensus on the key Ce species was reached in the literature using spherical CeO2 enclosed by (111) and (100) surfaces, not to mention the further control of its reaction specificity. In this study, octahedral and cubic CeO2 preferentially terminated by (111) and (100) surfaces were found to exhibit high reaction specificity (and activity) towards each of the above reactions. Spectroscopic evidence suggests that this is closely associated with the Lewis acidity (or electron density) of surface Ce species. The acidic Ce species on (111) surface can catalyze substrate dephosphorylation at room temperature but do not for substrate oxidation with H2 O2 . This correlation was further evidenced by the electron‐rich Ce species on (100) surface, hindering the first reaction while promoting the latter. Abstract : CeO2 nanosphere enclosed by (100) and (111) surfaces has been reported to mimic phosphatase and peroxidase by catalyzing substrate dephosphorylation and oxidation (with H2 O2 ). We herein successfully boost the reaction specificity for this material by shape control. The acidic Ce species on octahedron (111) surface was found to selectively catalyze substrate dephosphorylation while its electron rich counterpart on cube (100) surface only promotes substrate oxidation.